2023
DOI: 10.3390/molecules28207119
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of the Chemical Bonds of High-Valent Transition–Metal Oxo (M=O) and Peroxo (MOO) Compounds: A Historical Perspective of the Metal Oxyl–Radical Character by the Classical to Quantum Computations

Kizashi Yamaguchi,
Hiroshi Isobe,
Mitsuo Shoji
et al.

Abstract: This review article describes a historical perspective of elucidation of the nature of the chemical bonds of the high-valent transition metal oxo (M=O) and peroxo (M-O-O) compounds in chemistry and biology. The basic concepts and theoretical backgrounds of the broken-symmetry (BS) method are revisited to explain orbital symmetry conservation and orbital symmetry breaking for the theoretical characterization of four different mechanisms of chemical reactions. Beyond BS methods using the natural orbitals (UNO) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 259 publications
0
2
0
Order By: Relevance
“…Based on the observed chemoselectivity and high stereoselectivity, we anticipated a potentially fast tungstenooxaziridine addition across the alkene with formation of short-lived biradical species through homolytic cleavage of the N – O bond in the transition state. 21 Experiments with deuterated substrates showed that 2j1- d and 2p1- d reacted to provide 3j1- d and 3p1- d without any deuterium scrambling, thus both experiments confirming that a highly concerted syn -addition is likely to be the predominant pathway. We also wanted to address if 3 formed through hydrolysis of aziridine 5 under the reaction conditions, and we found that 5 j does not provide 3j under the reaction conditions.…”
Section: Resultsmentioning
confidence: 87%
“…Based on the observed chemoselectivity and high stereoselectivity, we anticipated a potentially fast tungstenooxaziridine addition across the alkene with formation of short-lived biradical species through homolytic cleavage of the N – O bond in the transition state. 21 Experiments with deuterated substrates showed that 2j1- d and 2p1- d reacted to provide 3j1- d and 3p1- d without any deuterium scrambling, thus both experiments confirming that a highly concerted syn -addition is likely to be the predominant pathway. We also wanted to address if 3 formed through hydrolysis of aziridine 5 under the reaction conditions, and we found that 5 j does not provide 3j under the reaction conditions.…”
Section: Resultsmentioning
confidence: 87%
“…Also, the higher reactivity of cobalt–oxo species may be due to the population of the anti-bonding π* orbitals on the M–O moiety which results in a relatively weak Co–O bond than the Fe–O bond. 59 b ,60 The second order perturbation analysis from the NBO basis of the metal–oxygen (M–O) bond indicated that species 1 has a higher stabilization energy (65.7 kcal mol −1 ) than species 2 (48 kcal mol −1 ). Here, we found that species 2 has weaker bonding between the metal and oxygen compared to species 1 .…”
Section: Resultsmentioning
confidence: 99%